Hubungan Kualitas Pelayanan terhadap Kepuasan Pasien Rawat Jalan BPJS dan Non BPJS di RSI Ibnu Sina Yarsi Padang Tahun 2025 - Annisa Apriani; Erlinengsih Erlinengsih; Putri Widya Herman (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
As the health insurance program, as one of the government’s efforts to fulfill the public’s right to health, continues to evolve, various phenomena related to patient satisfaction with the quality of hospital services often become current issues in society that can influence public perceptions of the quality of hospital services. This is also the case at RSI Ibnu Sina Padang, where a decline in BPJS outpatient visits and an increase in non-BPJS outpatient visits were observed. This study aims to determine the quality of service in relation to BPJS and non-BPJS outpatient satisfaction at RSI Ibnu Sina Padang in 2025. This research is a descriptive analytical study with a cross-sectional approach. The study was conducted at the outpatient facility of RSI Ibnu Sina Padang. The population was all 13,019 outpatients. Sampling was conducted using a purposive sampling technique with a sample size of 100 respondents. The analysis in this study includes univariate analysis and bivariate analysis using the chi-square test. The results of the study indicate that there is a relationship between service quality and satisfaction of BPJS outpatients (p = 0.018 and OR = 3.464) and there is a relationship between service quality and satisfaction of non-BPJS outpatients (p = 0.028 and OR = 17.250). It can be concluded that there is a significant relationship between service quality and satisfaction of BPJS and non-BPJS outpatients. It is expected that RSI Ibnu Sina Padang will always improve the quality of service and socialize to patients or the community about service procedures for both BPJS and non-BPJS patients